Adoption of Root and Tuber Technologies among Farmers (Agricultural Development Programme -Adp) - Ekwere, G. E; Edem, I. D.; Agbasi, O. E. (International Journal of Environment, 2014)
This paper analyzed the adoption rate of root and tuber technologies in Anambra state Agricultural Development Programme. Specific objectives were to ascertain the root and tuber expansion programme (RTEP) technologies, find out the extension methods and level of access to extension services among members of farmers based groups and to assess the farmers’ awareness on various varieties of root and tuber technologies. Three hypotheses were formulated to test the effect of variables on the adoption rate. Stratified random sampling techniques were used to determine the sample size of 112 including the farmers and RTEP staff. Findings showed that various varieties and technologies promoted in the area by RTEP were ABANA 85, ADAKA 96 and EKPE 88 for Yam, while TMS 305SS, TMS 30 and TMS 30572 for Cassava and White P. 179 and RED P. 162 for Potatoes. Comparatively the income levels of the farmers remained unchanged but they expressed satisfaction with the use of RTEP technologies. DOI: http://dx.doi.org/10.3126/ije.v3i4.11741 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page: 117-132